Implementasi Arsip Digital Untuk Penyimpanan Dokumen Digital - Ghifari Aminudin Fad’li; Marsofiyati Marsofiyati; Suherdi Suherdi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The development of technology in the digital era is currently so rapid that all kinds of human activities are very dependent on technological advances. Digitalization has penetrated all sectors of modern human life, including data archiving activities. Archives are very important for an organization or government if the archives are managed properly and correctly. Because the completeness of data and information is very dependent on the filing system. The purpose of this study is to determine the effect of implementing digital archives for storing digital documents. This type of research uses a qualitative approach. This qualitative research seeks to explore and understand different truths by different people. In a qualitative approach, one type of approach that is often used is the case study approach. The data analysis technique used is an interactive model data analysis technique. The results of this study explain the effects of implementing digital archives for storing digital documents.